2010
DOI: 10.1111/j.1468-0106.2010.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Housing in a Neoclassical Growth Model

Abstract: We present evidence that in the USA, the relative price of housing exhibits secular growth and that its growth rate is a stationary series. The ratio of the value of house stock to either consumption or GDP is also stationary. We develop a two-sector neoclassical growth model with housing that is consistent with these facts. Among the long-run determinants of the growth of housing prices and housing stock per capita are factor intensities, rates of technological progress in both the housing and non-housing sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…This section presents an endogenous growth model based on those proposed by Rebelo (1991), Leung (2001Leung ( , 2003, and Cheng et al (2010), in which the growth rates of the real GDP and house price are endogenously determined. This model provides theoretical underpinning for house price convergence.…”
Section: Endogenous Growth Model With the Housing Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…This section presents an endogenous growth model based on those proposed by Rebelo (1991), Leung (2001Leung ( , 2003, and Cheng et al (2010), in which the growth rates of the real GDP and house price are endogenously determined. This model provides theoretical underpinning for house price convergence.…”
Section: Endogenous Growth Model With the Housing Sectormentioning
confidence: 99%
“…(iii) Population: This study employs an endogenous growth model that assumes constant household population and land supply. Cheng et al (2010) relaxed this assumption and found that the steady-state growth rate of house price increases with the excess of population growth over land supply growth. Assuming that land supply is fixed (or population grows considerably faster than land supply), house price growth is expected to increase with population growth.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…5 Implicitly, this formulation assumes that there are potentially important interactions among the stock market, the housing market and the aggregate economy. For theoretical justifications, see Cheng et al (2010), Leung (2003Leung ( , 2007 and Leung and Teo (2009…”
Section: The Empirical Modelsmentioning
confidence: 99%
“…Pacific Economic Review (PER) is an appropriate choice for us as PER has previously published papers on housing market dynamics and its relationship with the aggregate economy (e.g. see Peng, Tam, & Yiu, ; Cheng, Li, & Zeng, ; Chang, Chen, & Leung, ).…”
mentioning
confidence: 99%